Penapisan Hipertensi Pada Kelurahan Tajur Sindang - Limanan, David; Edbert, Bruce; Shafira Putri, Nawaika; Halomoan Darma, Timothy (Universitas 17 Agustus 1945 Semarang, 2024)
Hypertension is a condition of increased systolic or diastolic blood pressure. Basic Health Research (Riskesdas) shows that the prevalence of hypertension nationally is increasing. The aim of this PKM is to check blood pressure and provide appropriate information about hypertension, so that it can prevent, screen, and carry out early intervention. The PKM include checking blood pressure and providing hypertension health counselling. The PKM was attended by 149 participants, with 57 male participants (38%) and 92 female participants (62%). Blood pressure examination showed that 50 participants had high blood pressure (34%). There were 19 male participants (33.3%) and 31 female participants (33.7%) who had high blood pressure. High sodium intake is one of the factors that causes hypertension. High fat diets and lack of physical activity will affect the elasticity of blood vessels, which leads to hypertension. High and uncontrolled blood pressure can cause strokes and heart attacks. So regular health checks need to be carried out.